Quality in the Implementation of School-Based Assessment in Ghana: Evidence from Business Studies Teachers - Bosu, Leticia; Agormedah, Edmond Kwesi; Anhwere, Daniel Kweku; Darkwa, Bernard Fentim; Ahmed, Andzie Tahir (American Journal of Social Sciences and Humanities, 2022)
The vitality and quality of implementing curriculum reforms and innovations depend on the teacher’s acceptance and concerns about the reforms and innovations. This research examines the concerns of Business Studies teachers about the quality of the implementation of School-Based Assessment (SBA) in the Senior High Schools in Central Region of Ghana. A descriptive, cross-sectional survey design was employed, and the census method involved all the Business Studies teachers. Data was gathered using the adapted Stages of Concern Questionnaire (SoCQ), processed via SPSS version 25.0 and analysed using Mean, Standard Deviations, Relative Intensity Percentile (RIP) and Factorial Multivariate Analysis of Variance (MANOVA). The study discovered that Business Studies teachers have the most intense concerns self-concerns (Awareness, Informational and Personal) least intense concerns at Impact concerns (e.g., Consequence) about SBA implementation in the curriculum. Further, the study established that Personal, Consequence, Collaboration and Refocusing Concerns significantly depend on teachers’ workload and SBA training. At the same time, gender, age, and years of teaching experience do not significantly influence teachers’ concerns about SBA implementation. The Business Studies teachers were not very much interested and involved in the SBA implementation. They are non-users and resistant to SBA implementation in the curriculum. The study recommended that the MoE/GES and NaCCA, in partnership with school administrators and GABET, should frequently organise ongoing training, workshops, seminars, conferences, and professional development courses for teachers to use and implement SBA in the curriculum. The MoE/GES should provide SBA logistics (tools, equipment) and materials needed for SBA implementation.